1962
DOI: 10.1021/jf60123a003
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Drop Control Residues, Determination of Naphthaleneacetic Acid in Apples

Abstract: For the determination of naphthaleneacetic acid (NAA) in apples, the compound is extracted with dilute alkali and separated from interfering materials by partition chromatography on a silicic acid column. Both ultraviolet absorption at 283 mp and a colorimetric procedure are used for measuring residues. The ultraviolet method is sensitivite to 0.1 p.p.m., and recoveries averaged 93.5%. The colorimetric procedure is sensitive to 0.2 p.p.m., and recoveries averaged 79.1 %. Residues of the chemical were less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Until now, sensitive methods of residue analysis for NAAamide have been unknown. For NAA, however, a previously reported uv absorption and colorimetric method could detect residues as low as 0.2-0.1 ppm in apples (Bache et al, 1962). Similar procedures were developed for olives (Zweig et al, 1964) and for pineapple (Young et al, 1963) with a sensitivity of 0.03 ppm.…”
mentioning
confidence: 94%
“…Until now, sensitive methods of residue analysis for NAAamide have been unknown. For NAA, however, a previously reported uv absorption and colorimetric method could detect residues as low as 0.2-0.1 ppm in apples (Bache et al, 1962). Similar procedures were developed for olives (Zweig et al, 1964) and for pineapple (Young et al, 1963) with a sensitivity of 0.03 ppm.…”
mentioning
confidence: 94%
“…Shindy et al (1973) found when Kinnow mandarin fruits were dipped in aqueous solutions of [14C]-a-naphthaleneacetic acid and extracts of the tissue were analyzed that a significant amount of the NAA was converted into NAAsp and NAGlu. Several investigators have previously published methods for the analysis of NAA by electron affinity (Bache et al, 1964), ultraviolet absorption (Bache et al, 1962), and high-performance liquid chromatography (Co-chrane and Lanouette, 1972; Moye and Wheaton, 1979), but the conjugates NAAsp and NAGlu would not have been detected primarily due to the methods of extraction as well as the cleanup procedures.…”
mentioning
confidence: 99%